PENGARUH EKSPOR MIGAS DAN NON MIGAS TERHADAP PRODUK DOMESTIK BRUTO INDONESIA - Mashur Razak; M. Ihsan Indra Jaya (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2014)
This research aims to know the influence of oil and gas and non oil and gas exports towards the gross domestic product. The object of the research is in Indonesia and the data used in this study in 2008-2012. Analysis techniques were used to test the hypothesis of this research is the multiple regression analysis and data processing in the research using SPSS. The results of this research indicate that oil and gas exports and the export of non-oil and gas together positive and significant effect on gross domestic product of Indonesia. While the test is partially or singly showed different results, where oil and gas export variables have no effect partially against Indonesia gross domestic product, this is due to not over oil and gas export value and gross domestic product of Indonesia, in addition to other variables being up or down significantly and is one of the variable counter in search of the value of gross domestic product. On the other hand in partially test indicates that the variable is non-positive and influential oil & gas significantly to gross domestic product of Indonesia.